Take The Lead : how women leaders are driving success through innovation - Corboz, Anne-Valerie (London: New York: New Delhi: Kogan Page, 2024)
"Only 26% of leadership positions in business are occupied by women. This book explores how we can close this prevailing gender gap before offering practical strategies on how you can Take the Lead as a business leader. Combining academic rigour with corporate expertise, this book features first-hand research and interviews with female leaders within global organizations to offer the strategies and insights that will propel you to success. From managing conflict and building confidence to growing your network and shaping your career, Take the Lead offers the strategies and inspiration you need to boost your leadership skills and establish yourself as a successful and influential changemaker."
Keywords: Leadership in Women; Women Executives; Women -- Vocational Guidance; Self-help Publications